Observation of the ?b 0?J/??? decay in proton-proton collisions at s=13TeV - Sirunyan, A. M.; Tumasyan, A. R.; Adam, W.; Ambrogi, Federico; Bergauer, Thomas; Dragicevic, Marko; Erö, Janos (Elsevier B.V., 2020)
The observation of the ?b 0?J/??? decay is reported using proton-proton collision data collected at s=13TeV by the CMS experiment at the LHC in 2018, corresponding to an integrated luminosity of 60fb?1. The ratio of the branching fractions B(?b 0?J/???)/B(?b 0??(2S)?) is measured to be (8.26±0.90(stat)±0.68(syst)±0.11(B))×10?2, where the first uncertainty is statistical, the second is systematic, and the last uncertainty reflects the uncertainties in the world-average branching fractions of ? and ?(2S) decays to the reconstructed final states. © 2020 The Author
Keywords: b physics; CMS; Computing; Heavy-flavor spectroscopy